From Majapahit to Putrajaya searching for another Malaysia - Farish A. Noor (Farish Ahmad Noor) 1967- (Silverfishbooks, 2005)
The essays in this collection - a real bunga rampai, a wonderfully varied bouquet of flowering polemics - are the work, and demonstrate the working, of a singular mind, one that is recognizably Malay and Malaysian, grounded in this country and its historical trajectory, yet elegantly cosmopolitan. They engage alike with the latest political controversies; with long and perhaps wilfully forgotten historical events; with public identities of widely recognized symbolic standing and with significant but scarcely known individual personalities. Farish's accounts of these matters are both personal and political, impassioned and analytical, born of intensely private feelings - often those of anguish and dismay, bewilderment and outrage - yet at the same time generously, even recklessly, public-spirited. Forthright, controversial, courageous, Farish Noor's is no ordinary voice. His writings about religious extremism and 'moral panic' on social conformity and the 'new generation post-modern Malay', make his an indispensable voice and viewpoint these days. -- Clive Kessler, Emeritus Professor, School of Sociology and Anthropology, UNSW Sydney